Liquid-assisted grinding mechanochemical approach for direct amidation of pyridone-carboxylic acid to synthesize an intermediate used in anti-viral API's bictegravir and cabotegravir - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ChemistrySelect, 2026)
Mechanochemistry is viewed as an appealing alternative for the synthesis of various compounds, since it is regarded as an eco-friendly and economical method that can be performed under solvent-free reaction conditions. In this work, neat grinding and liquid-assisted grinding (LAG) methods for direct amidation of pyridone-carboxylic acid and 2,4,6-trifluorobenzylamine/2,4-difluorobenzylamine were studied using EDC.HCl as a coupling reagent to synthesize important intermediates used in the synthesis of anti-HIV drug molecules bictegravir, cabotegravir, and dolutegravir. The products were easy to separate as they easily precipitated out from water, and the purity of the products obtained was similar to 97% for the intermediates, thus avoiding the need for their purification. This process eliminated the use of organic solvents for the reaction as well as for the work-up and product purification. The reaction was scaled up on a 15-g scale, giving good yields of the intermediates. The process was found to be practical, scalable, and reproducible on a gram scale.
Keywords: amidation; bictegravir; cabotegravir; mechanochemistry